Perception and Prevalence of Bullying in Malaysian Higher Education: A Multifaceted Analysis - Amran Abdul Halim; Ahmad Sanusi Azmi; Norazmi Anas; Zulkifli Mohd Ghazali; Mohd Ahsani A. Malek; Ishak Suliaman; Shahril Nizam Zulkipli (Institute of Advanced Science Extension (IASE), 2024)
Indexed by WOS/ Scopus